2022
DOI: 10.3390/w14233880
|View full text |Cite
|
Sign up to set email alerts
|

Study on Waterlogging Reduction Effect of LID Facilities in Collapsible Loess Area Based on Coupled 1D and 2D Hydrodynamic Model

Abstract: The accurate evaluation method of LID toward the attenuation of urban flood is still a hot issue. This paper focuses on a coupled 1D and 2D hydrodynamic model, investigating the model parameters set in a collapsible loess area, and the changes in the surface runoff, waterlogged area, and drainage network indicators under different rainfall patterns. The results show that the coupled model can effectively simulate the effect of LID facilities under unaltered and retrofitted conditions. It is found that the infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…With R2E, the effectiveness of the systems Type 5 a declines significantly. It is widely known in the literature that the effectiveness of NBSs for flood mitigation decreases with more intense rain events [15,16,27]. However, infiltration systems of Type 100 a can still effectively reduce flooding and achieve almost three times the flood reduction compared to systems such as Type 5 a.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With R2E, the effectiveness of the systems Type 5 a declines significantly. It is widely known in the literature that the effectiveness of NBSs for flood mitigation decreases with more intense rain events [15,16,27]. However, infiltration systems of Type 100 a can still effectively reduce flooding and achieve almost three times the flood reduction compared to systems such as Type 5 a.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the performance of NBSs in flood reduction, mainly models are used due to the lack of data from actual field measurements or other data [13]. The Storm Water Management Model (SWMM) [14] is widely used for the representation of NBSs with their LID elements [15,16]. Numerous studies have utilized the observed data from experimental NBSs to validate and calibrate the LID model approach in SWMM [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations